Karakteristik Habitat Larva Nyamuk dan Kepadatan Nyamuk Dewasa (Diptera: Culicidae) di Kabupaten Jembrana, Provinsi Bali (Analisis Data Sekunder Rikhus Vektora 2017): Habitat Characteristics of Mosquito Larvae and Density of Adult Mosquitoes (Diptera: Culicidae) in Jembrana Regency, Bali Province (Rikhus Vektora 2017 Secondary Data Analysis) - Wahono, Tri; Widjayanto, Dionisius; Poerwanto, Soenarwan Hery (Aspirator, 2022)
Abstract. Mosquitoes play a direct role in the spread of various vector-borne diseases in tropical countries. The three main mosquito genera that spread disease in Indonesia are Aedes, Culex, and Anopheles. Jembrana Regency, Bali Province is an endemic area for dengue, malaria, and filariasis. Jembrana Regency is still reporting cases of DHF, malaria and is in the stage of administering filariasis mass prevention drugs in 2020. Control of mosquito vectors is influenced by various things, such as the specific habitat of the larvae and the density of adult mosquitoes. The study used data from Rikhus Vektora 2017 in Jembrana Regency, Bali Province by characterizing specific habitats, measuring water parameters, calculating mosquito density with the Man Hour Density formula, and measuring environmental parameters in all types of ecosystems. Specific habitat of Aedes sp. in the form of a puddle of freshwater that is not in contact with the ground, Culex sp. in the form of a puddle of fresh water in contact with the ground, and Anopheles sp. a pool of fresh-brackish water in contact with the ground with different water parameters but still in a close range. The mosquito density was dominated by Culex sp. in all ecosystems except for coastal ecosystems close to settlements dominated by Aedes sp. All adult mosquitoes (Aedes sp., Culex sp., and Anopheles sp.) in Jembrana Regency are more zoophilic. The behavior of all adult mosquitoes is different in each ecosystem, which can be endophagic or exophagic. Environmental parameters in Jembrana Regency have the potential to support mosquito breeding. Abstrak. Nyamuk berperan langsung dalam penyebaran berbagai penyakit tular vektor di negara tropis. Tiga genus nyamuk utama penyebaran penyakit di Indonesia adalah Aedes, Culex, dan Anopheles. Kabupaten Jembrana, Provinsi Bali merupakan daerah endemis untuk DBD, malaria maupun filariasis. Kabupaten Jembrana masih melaporkan kasus DBD dan malaria serta dalam tahap pemberian obat pencegahan massal filariasis pada tahun 2020. Pengendalian vektor nyamuk dipengaruhi berbagai hal seperti karakteristik habitat larvanya dan kepadatan nyamuk dewasa. Penelitian menggunakan data Rikhus Vektora 2017 di Kabupaten Jembrana, Provinsi Bali dengan melihat karakteristik habitat larva, pengukuran parameter air, dan kepadatan nyamuk dengan perhitungan Man Hour Density, serta pengukuran parameter lingkungan pada semua tipe ekosistem. Habitat larva Aedes sp. berupa genangan air tawar yang tidak bersentuhan dengan tanah; Culex sp. berupa genangan air tawar bersentuhan dengan tanah; dan Anopheles sp. genangan air tawar-payau yang bersentuhan dengan tanah dengan parameter air yang berbeda, namun masih dalamrentang yang tidak jauh. Kepadatan nyamuk didominasi oleh Culex sp. di semua ekosistem kecuali pada ekosistem pantai dekat dengan pemukiman didominasi oleh Aedes sp. Semua nyamuk dewasa (Aedes sp., Culex sp., dan Anopheles sp.) di Kabupaten Jembrana lebih bersifat bersifat zoofilik. Perilaku semua nyamuk dewasa berbeda di setiap ekosistem, dapat bersifat endofagik maupun eksofagik. Parameter lingkungan di Kabupaten Jembrana memiliki potensi untuk mendukung perkembangbiakan nyamuk.